Achievement of ODF (Open Defecation Free) Villages Through the Social Functions Approach In Teba Village - yuni ratnasari; Tria Fadilla; Suwaib Amiruddin (Universitas Andalas, 2023)
Public behavior of open defecation free (ODF) is an unhealthy condition. The program through ownership of healthy latrines is presented as a means of educating the public about healthy living. The research aims to determine the social structures in achieving ODF (Open Defecation Free) villages. This study uses qualitative methods with the aim of seeing the location first hand and conducting interviews for the individuals and groups involved. The results of the study show that the ODF program involves several components including the company, government and community. The function of the community is to form groups for sanitation socialization, while the company participates in building both latrines and clean water facilities. Meanwhile, Pekon Teba also provides facilities, in accordance with government programs that have been planned, both in terms of budget and additional facilities. The facilities and infrastructure provided to the community include repairing waterways by establishing a Clean Water Facilities Management Agency (BPSAB) together with YKWS and PT. Tirta Investama while from a budget perspective it is fully supported by CSR PT. Tirta Investama and policies in the form of sanctions limit access to public services for residents who are reluctant or refuse to build healthy latrines in their respective homes.